Attitudes towards Death, Perceptions of Hospice Care, and Hospice Care Needs among Family Members of Patients in the Intensive Care Unit - Oak, Yunha; Kim, Young-Sun (Han'guk Hosup'isu Wanhwa Uiryo Hakhoe chi = The Korean journal of hospice and palliative care, 2020)
This study aimed to identify the relationships among attitudes towards death, perceptions of hospice care, and hospice care needs as perceived by family members of patients in the intensive care unit (ICU). This study used a descriptive correlational method. A structured questionnaire was used to collect data from 114 participating families in the ICU at Dong-A University Hospital, from October 10 to November 1, 2019. The data were analyzed in terms of frequency, percentage, and mean and standard deviation. The t-test, one-way analysis of variance, and Pearson correlation coefficients were also conducted. Perceptions of hospice care showed significant differences according to age (F=3.06, P=0.031) and marital status (t=3.55, P=0.001). However, no significant differences in attitudes towards death or hospice care needs were found. A significant positive correlation was found between perceptions of hospice care and hospice care needs (r=0.49, P<0.001). In order for families to recognize the need for hospice care and to receive high-quality palliative care at the appropriate time, it is necessary to increase public awareness of hospice care through various educational and awareness-raising efforts, thereby providing opportunities for families of terminally ill patients to request hospice care.